PENERAPAN WARNA DAN MATERIAL PADA AREA BERMAIN PLAYTOPIA - Cordellia Ivana; Sakundria Satya Murti Wardhana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Play areas such as Playtopia are not merely places for entertainment. They are also designed as facilities to stimulate children’s motor, cognitive and social development. This study examines the use of color and materials in the Playtopia play area as interior design elements that contribute to enhancing children’s activity stimulation. The results of direct observation, visual documentation and analysis of color and material theory suggest that the selection of bright and contrasting color (yellow, blue, red, and green) can stimulate positive emotions and encourage children to be more active and exploratory. Meanwhile, the use of safe, soft and impact-resistant materials supports children’s safety and comfort. The appropriate combination of colors and materials can create a pleasant, safe atmosphere that supports the learning process through play. Therefore, the application of color and materials has a significant influence on enhancing children’s activity stimulation in play areas and is an important aspect in the design of modern education and recreational interiors, such as Playtopia